SOES CORPORATE PERFORMANCE ON IDX AND SOME INFLUENCED FACTORS - Iba, Zainuddin; Syahputra, Yudi; Syamni, Ghazali; Mahdawi, Mahdawi (Jurnal Aplikasi Manajemen, 2021)
State-owned enterprises are government-owned businesses that have been privatized and can be close to politicians from political parties. They are also notorious for being poorly managed. The purpose of this research is to examine how political connections, institutional ownership, cash holdings, company size, and leverage affect the performance of state-owned enterprises on the Indonesia Stock Exchange. The data for this study comes from the annual reports of 20 state-owned enterprises (SOEs) listed on the IDX from 2014 to 2018. This research model is a panel regression model that tests the common effect, fixed-effect, and random effect models. Based on the Chow test and Hausman test, the best model in this study is the random effect model. The results found that political connections, institutional ownership, and cash holding are significant factors affecting the performance of state-owned companies. Another finding was that companies with stronger political connections affect the performance of state-owned companies. On the other hand, this study did not find companies having political connections affect the performance of state-owned companies. This finding is expected to provide benefits for investors to consider SOEs companies to invest.